2022
DOI: 10.3390/cancers14092087
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Local Photon Irradiation Is Crucial in Anti-CTLA-4 Antibody Therapy to Enhance the Abscopal Response in a Murine Pancreatic Carcinoma Model

Abstract: Pancreatic cancer is an extremely treatment-resistant neoplasm to chemotherapy and immunotherapy. The combination of photon beam irradiation and anti-CTLA-4 antibody (C4) for the anti-tumor effect enhancement at local and distant tumors (abscopal tumors) was investigated using the pancreatic ductal adenocarcinoma (PDAC) mouse model. Pan02 cells were bilaterally inoculated to both legs of C57BL/6 mice. High dose photon beams in a hypofractionation or a single fraction were delivered to the tumors on one leg. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Alpha radiation treatment appears therefore to induce an immune response through immunogenic cell death, with enhanced efficacy in combination with check-point inhibition. This has been previously reported with other methods of irradiation in combination with check point inhibition ( 47 ).…”
Section: Discussionsupporting
confidence: 81%
“…Alpha radiation treatment appears therefore to induce an immune response through immunogenic cell death, with enhanced efficacy in combination with check-point inhibition. This has been previously reported with other methods of irradiation in combination with check point inhibition ( 47 ).…”
Section: Discussionsupporting
confidence: 81%
“…Previous clinical reports demonstrated that neoadjuvant chemoradiotherapy increased the proportion of CD8 + T cells in the whole lymphocytes in other tumors (22,23). A recent preclinical study using a pancreatic ductal carcinoma mouse model demonstrated that local irradiation at 16 Gy in a single fraction and three fractions of 8 Gy increased not only Teff but also Treg in irradiated tumors, indicating that radiation altered the tumor immune microenvironment to immune evasion as well as immune activation (24). Similarly, in a colon cancer mouse model, radiation at 12 Gy in a single fraction clearly promoted the accumulation of Treg (25).…”
Section: Discussionmentioning
confidence: 94%
“…This was due to IFN-I mediated DC infiltration, CD8 + cross priming, and subsequent effector CD8 + T cell infiltration into the TIME (191,192). Such antitumor response was consistently observed when RT was combined with an anti-CTLA-4 ICI in vivo (193)(194)(195)(196). The intensity of an abscopal response generated from such combinations are dose fractionation and treatment sequence dependent.…”
Section: Augmenting Antitumor Immunity By Combining Radiotherapy With...mentioning
confidence: 97%
“…When compared with concurrent delivery of RT and an anti-CTLA-4 ICI, ICI delivery after RT was shown to have reduced distant therapeutic effect. Increased antitumor immunity with the combined treatment is associated with increased CTLs, CD8/CD4 ratio, reduced Tregs within the TIME, and increased CD8 + T cell clonality ( 195 , 196 ).…”
Section: Augmenting Antitumor Immunity By Combining Radiotherapy With...mentioning
confidence: 99%